Preparation and Characterization of Carbon/Si Nanocomposites Synthesized by Chemical Vapor Deposition (CVD) Using SiC and SiO2 - Alaa Keshtta; Retno Duwi Hardini; Teguh Endah Saraswati; Sentot Budi Rahardjo (ALCHEMY Jurnal Penelitian Kimia, 2024)
Carbon-based nanocomposite materials have attracted the attention of researchers in the last decade due to their unique properties applicable in wide applications. This study aims to synthesize and study the characteristics of the carbon-based nanocomposite material produced using the chemical vapor deposition (CVD) method with SiC and SiO2. The CVD process was carried out at 900 ℃ in a vacuum with flowing argon, hydrogen, and acetylene gases. The CVD process produced nanocomposites with more sp3 hybridized carbon atoms, as indicated by the D peak in the Raman spectra. The diffraction pattern analyses show that the resulting carbon powder nanocomposite growth with SiC powder (CSiC) reveals a carbon diffraction peak C(002) and has an elongated form confirmed by an electron microscope. In comparison, the resulting carbon powder nanocomposite growth with SiO2 powder (CSiO2) has a spherical form and presents a carbon diffraction peak C(002). CSiC nanocomposites showed both symmetric and asymmetric C‒H stretching. In FTIR data, CSiO2 nanocomposites show more intense O‒H group peaks but lower-intensity C‒H group vibrations.